Namalycastis occulta n. sp. and a new record of N. borealis (Polychaeta: Nereididae: Namanereidinae) from the Northwestern Caribbean Sea - Conde-Vela, Víctor Manuel (Zootaxa, 2013)
The nereidid polychaete genus Namalycastis Hartman, 1959 has been recorded almost exclusively in non-marine environments. This genus includes species having four pairs of tentacular cirri, and its species mainly differ by the relative size of dorsal cirri in posterior chaetigers. Namalycastis occulta n. sp. is described based upon non-mature and mature specimens collected in the intertidal from Chetumal Bay, Quintana Roo, Mexico. Its distinctive features are the lack of notopodial spinigers, eyes, and teeth in the mandibles. Namalycastis borealis Glasby was found in Tamalcab Island, Chetumal Bay and it is the first record for Mexico. Analyses of the intraspecific variability, a key to the known species in the Grand Caribbean region, and commentaries about some taxonomic topics are also included.